2017
DOI: 10.1111/1759-3441.12185
|View full text |Cite
|
Sign up to set email alerts
|

Ownership Structure and Firm Performance Improvement: Does it Matter in the Vietnamese Stock Market?

Abstract: This study examines the effects of ownership structure on firm performance of manufacturing companies listed on the Ho Chi Minh Stock Exchange using the system‐GMM estimator. The empirical results show a cubic relationship between managerial ownership and Tobin's Q, that is, positive, negative and positive, meanwhile block ownership has no impact on firm performance. This implies that internal managerial incentives play a more important role than shareholders' external monitoring in improving corporate governa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
35
4
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 66 publications
10
35
4
2
Order By: Relevance
“…This relationship has also been considered in emerging markets such as Thailand (Kim et al, 2004), Malaysia (Haniffa and Hudaib, 2006). In Vietnam, Hoang et al (2017), Phung and Mishra (2016), Vu et al (2018), and Tran and Le (2020) are closest in spirit to our study. However, Phung and Mishra (2016) and Vu et al (2018) do not examine the effect of both block ownership and managerial ownership on corporate performance.…”
Section: Introductionsupporting
confidence: 56%
See 3 more Smart Citations
“…This relationship has also been considered in emerging markets such as Thailand (Kim et al, 2004), Malaysia (Haniffa and Hudaib, 2006). In Vietnam, Hoang et al (2017), Phung and Mishra (2016), Vu et al (2018), and Tran and Le (2020) are closest in spirit to our study. However, Phung and Mishra (2016) and Vu et al (2018) do not examine the effect of both block ownership and managerial ownership on corporate performance.…”
Section: Introductionsupporting
confidence: 56%
“…Haniffa and Hudaib (2006) find no linkage between changes in managerial shareholdings and subsequent market performance in the Malaysian market. In Vietnam, Hoang et al (2017), Tran and Le (2020) find no statistical significance of a linear relationship between block ownership and corporate performance. Kim et al (2004) tend to newly listed Thai firms to emphasize the importance of managerial shareholdings in emerging markets and indicate the positive effect of managerial shareholdings on corporate performance.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 93%
See 2 more Smart Citations
“…Galego et al, (2019) found a positive relationship between managerial ownership and firm performance where managers are the part of higher management and the corporate board. Another method of finding the relationship between ownership structure and firm performance was introduced by Hoang et al, (2017) using the simultaneous equation model and considering both firm performance and ownership structure as endogenous. They found that managerial ownership was a positive predictor of Q and that Q is a significant negative predictor of managerial ownership.…”
Section: Literature Reviewmentioning
confidence: 99%